2006
DOI: 10.1358/mf.2006.28.8.1003577
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacological action of vitamin E unrelated to its antioxidant capacity

Abstract: The pharmacological action of vitamin E on the mechanical activity of isolated guinea pig colonic smooth muscle was examined in normoxic and hypoxic conditions. In hypoxia, but not normoxia, alpha-tocopherol (1-160 microM) evoked rapid concentration-dependent contractions from the colon. This was also seen with other members of the vitamin E family, and potency measurements gave EC(50) values (microM) of 10.6 +/- 0.9 for D-alpha-tocopherol, 6.0 +/- 1.2 for D-beta-tocopherol, 7.5 +/- 0.7 for D-gamma-tocopherol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previously, we have reported that trolox reduces the amplitude of duodenal spontaneous contractions but it does not alter their frequency (34). In normoxia, addition of a-tocopherol produces no discernible effects on the frequency of contractions in guinea-pig colon (35). Vitamin E decreases contractions induced by 400 mM of ethanol in isolated canine cerebral vascular rings (36).…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we have reported that trolox reduces the amplitude of duodenal spontaneous contractions but it does not alter their frequency (34). In normoxia, addition of a-tocopherol produces no discernible effects on the frequency of contractions in guinea-pig colon (35). Vitamin E decreases contractions induced by 400 mM of ethanol in isolated canine cerebral vascular rings (36).…”
Section: Discussionmentioning
confidence: 92%